Prevalence of Barrett's esophagus in Lebanon - Masri, Omar; Ibrahim, Feras; Badreddine, Rami; Chalhoub, Jean M.; Sharara, Ala I. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To determine the prevalence of Barrett’s Esophagus (BE) in a tertiary care center in Lebanon and to compare IT with regional and global data. Materials and Methods: All esophagogastroduodenoscopies (EGDs) performed between January 2003 and October 2013 at the American University of Beirut Medical Center (AUBMC) were reviewed, and cases of endoscopically suspected esophageal metaplasia (ESEM) were identified. Definite BE was considered only if histologically proven intestinal metaplasia was present. Results: Totally, 16,787 patients underwent EGD; 219 patients (1.3%) were labeled as having ESEM. Only 41 patients had biopsyproven BE (18.7% of ESEM and 0.24% of total patients). The mean age of the patients with BE was 58.1 years [Standard deviation (SD) =13.7] and 78% were men. Of the 41 patients, 14 (34.1%) had long-segment BE (LSBE) (>3 cm) while 27 had short segment Barrett’s Esophagus (SSBE) (≤3 cm). Hiatal hernia was identified in 54% of the patients, more commonly in those with LSBE. Only four patients had low-grade dysplasia, and none had high-grade dysplasia. Conclusion: The prevalence of BE in Lebanon is much lower than that in Western countries. The reasons for this East-West divide are unknown and require further investigation.